Artificial Intelligence: The Next Frontier in Pharmacy Automation and Drug Dispensing - Aswini A, Jamdhade; Prerana B, Jadhav; Ishwari D, Gosavi; Bhumika P, Ghate; Rupali B, Shinde; Divya, Patni; Ashwini, Rashinkar (Journal of Neonatal Surgery, 2025)
The integration of artificial intelligence (AI) into various healthcare domains has revolutionised traditional practices, such as medication work. This section looks on the use of AI in trade activities for medicine dispensing, with an eye towards how it might improve performance and safety in medical settings. Through the analysis of patient data, including medical history, allergies, and medication interactions, artificial intelligence (AI) technologies like machine learning and natural language processing are being used to enhance drug dispensing procedures. By guaranteeing proper medication administration, AI systems can assist chemists in making well-informed judgements regarding drug delivery dosage adjustments and medication reconciliation, which not only reduces the possibility of mistakes but also enhances patient outcomes. However, AI-powered automation tools enhance pharmacy inventory management and prescription fulfilment operations. These systems can estimate medicine request reminder stock levels and automate refills, minimising waste and stock outs while also ensuring that patients have easy access to critical prescriptions. AI dramatically increases patient safety when delivering medications. This proactive approach lowers the likelihood of prescription errors, which results in fewer hospital readmissions and antagonistic drug events. However, concerns like data privacy, algorithmic program bias, and regulatory conformance must be addressed in order to fully realise the benefits of AI in medicine dispensation. Lastly, the use of AI in medication dispensing procedures has great potential to luxuriate productivity and security in the medical environment. AI systems can detect potential adverse drug reactions, drug interactions, and dosage errors in real time, notifying healthcare providers and enabling them to substitute promptly.